Investigation of the vocational experience periods of the UEFA champions league winner team head coaches - Bahadir Bayarslan (ROL Spor Bilimleri Dergisi, 2023)
The aim of this research is to investigate how long it takes to turn success into a competency for the elite football coaches who won the UEFA Champions League Finals, taking into account the importance of their professional experience. The model of the research was determined as “Basic Qualitative Research”, and the data collection technique in the research was determined as “Document Analysis”. The analysis of the data in the research was made according to the Miles and Huberman model as a descriptive analysis. The universe of the research consists of the teams that won the UEFA Champions League Finals from 1993 to 2022. Its sample is the coaches of the teams that won the UEFA Champions League between 1993-2022. The sampling method of the research is density sampling based on heuristic approach. When the general and active working times of all the coaches who won the UEFA Champions League final from 1993 to 2022 are examined, it is seen that although the average of the coaching experience of the group is high, the champions in the first years of their coaching career are numerically superior to the experienced coaches. As a result, it has been understood that the length of the coaching experience is not a factor that directly affects the success.